2021
DOI: 10.1002/ps.6729
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of key parameters for developing a Metarhizium rileyi‐based biopesticide against Spodoptera frugiperda (Lepidoptera: Noctuidae) in maize: laboratory, greenhouse, and field trials

Abstract: BACKGROUND: The entomopathogenic fungus Metarhizium rileyi is known to cause natural infections in some caterpillars. In this multiyear study, we carried out laboratory, greenhouse and three field trials with the aim of developing a sustainable option for control of the fall armyworm (FAW) in maize. Association of M. rileyi with Spodoptera frugiperda baculovirus (SfMNPV) and delivery strategies were also investigated. RESULTS: The selected isolate (CG381) was effective in the laboratory at a low concentration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 46 publications
(79 reference statements)
1
15
0
3
Order By: Relevance
“…Alternatively, a large number of studies have shown that B. bassiana is pathogenic to S. frugiperda [ 35 , 36 ], and that B. bassiana could be compatible with natural enemies to improve the control effect [ 37 ]. Therefore, entomopathogenic fungi could be prime substitutes for insecticides [ 38 , 39 ]. However, most entomopathogenic isolates show high mortality only to young larvae but low pathogenicity to old larvae [ 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, a large number of studies have shown that B. bassiana is pathogenic to S. frugiperda [ 35 , 36 ], and that B. bassiana could be compatible with natural enemies to improve the control effect [ 37 ]. Therefore, entomopathogenic fungi could be prime substitutes for insecticides [ 38 , 39 ]. However, most entomopathogenic isolates show high mortality only to young larvae but low pathogenicity to old larvae [ 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…The OD formulation had some advantages, such as increasing the rate of the infection process and reducing the time to kill the host (lower ST 50 ), despite no significant difference in the reduction in survival time relative to that observed for unformulated conidia. The advantages of oil-based formulations in enhancing the infectivity of the selected strains of M. rileyi [9,19,20,23] and reducing damage to plants [22] have been reported in other studies. Emulsifiable oils facilitate biopesticide manipulation by the end user as an alternative to formulate highly hydrophobic dry conidia of M. rileyi.…”
Section: Discussionmentioning
confidence: 52%
“…Simple formulations may protect conidia from abiotic stressors, as previously reported for species in the Metarhizium anisopliae complex [15][16][17], including the negative effects of some chemical fungicides [18]. For the fungus M. rileyi, only experimental low-cost formulations have been tested under laboratory conditions [19][20][21], greenhouse [22], and field conditions [9,23]. However, information on how these formulations may protect M. rileyi conidia from the negative effects of the chemical fungicides used in soybean crops is unavailable.…”
Section: Introductionmentioning
confidence: 99%
“…The virulence of M. rileyi depends on the host insect species, developmental stage, fungal strain, spore concentration, and experimental conditions (Dutta et al, 2014; Faria et al, 2022; Montecalvo et al, 2022; Shylesha et al, 2018; Zhou et al, 2020). Bosa et al (2004) evaluated the susceptibility of FAW to 10 strains of M. rileyi , finding that the mortality ranged from 73% to 100%.…”
Section: Discussionmentioning
confidence: 99%
“…The virulence of M. rileyi was evaluated as described by Faria et al (2022) with some modifications. Fourth‐instar larvae of FAW ( n = 6/replication) were inoculated by spraying with M. rileyi conidial suspension (1 × 10 7 /ml) prepared in distilled water with a surfactant (Tween‐80, 0.05% v/v).…”
Section: Methodsmentioning
confidence: 99%